The Global Bank Stress Test - Ding, Xiaodan; Gross, Marco; Krznar, Ivo.; Laliotis, Dimitrios; Lipinsky, Fabian (Washington, D.C. : International Monetary Fund, 2022)
This paper presents the framework underlying the Global Bank Stress Test (GST) and applies it to recent data and global scenarios to illustrate the usefulness of the framework in assessing the potential impact of global shocks on banks around the world. The results of this latest update of the GST continue to point to relatively lower levels of resilience of banks in emerging market economies (EMs) than in advanced economies (AEs).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Banks; Depository Institutions; Financial Crises; Financial Institutions and Services; Micro Finance Institutions